Livro didático de geografia: a relação sociedade natureza nos anos finais do ensino fundamental - Ferreira, Wattson Estevão (2018)
In recent years, the concerns about the didactic book have been marked by scientific debates in meetings and congresses, discussing the elaboration and production of these materials, according to the new proposals for education, contemplating the Teaching of Geography. In this context, this research has as general objective, to understand how the concept Relation Society and Nature is approached in the textbooks of Geography, used in Primary Education and the specific ones: to discuss the concept of nature and society; verify if the content found is in accordance with the initial proposal, the edicts of the National Textbook Program; to identify the concepts of Relation Society and Nature in the textbooks of Geography used in Elementary School. In this qualitative research, with bibliographical review and documentary analysis, we have examined research already done in the area, in books, journals, and in the Capes database, besides official documents of the policies destined for the elaboration and production of the books, made available on sites linked to the federal government, aiming to unveil the subject in question. The books to be analyzed are two works of the 6th year of elementary school, in which they were analyzed: how they deal with the concept of Relation Society and Nature and the conformity with the PNLD edicts. It should be emphasized that this research does not intend to underestimate the authors of the materials or the program, which made the materials available to the schools, the real intention is that the criticisms pointed out be used in future revisions enabling the elaboration of better textbooks, contributing to the training of students. We conclude that the textbook is not only a simple material delivered to the students, in the process of teaching and learning, there are some misconceptions about the textbook, first in the sense of discussing its use or not, in some cases, this may be the single access to a book during a good part of the subjects' lives, or the only pedagogical resources of teachers in some localities of the country.